Association of serum markers of oxidative stress with incident major cardiovascular events, cancer incidence, and all-cause mortality in type 2 diabetes patients: pooled results from two cohort studies - Xuan, Yang; Gao, Xin; Anusruti, Ankita; Laetsch, Dana Clarissa; Brenner, Hermann; Schöttker, Ben (Diabetes care, 2019)
OBJECTIVE: Oxidative stress plays an important role in the pathophysiology of type 2 diabetes mellitus (T2DM). However, associations of biomarkers of oxidative stress with diabetes complications have not yet been addressed in large cohort studies. - RESEARCH DESIGN AND METHODS: Derivatives of reactive oxygen metabolites (d-ROMs) levels, a proxy for the reactive oxygen species burden, and total thiol levels (TTLs), a proxy for the reductive capacity, were measured in 2,125 patients with T2DM from two German cohort studies of almost equal size at baseline and 3-4 years later. Multivariable adjusted Cox proportional hazards models with time-dependent modeled d-ROMs levels and TTLs were used to assess the associations with incident major cardiovascular events (MCE), cancer incidence, and all-cause mortality. - RESULTS: In total, 205, 179, and 394 MCE, cancer, and all-cause mortality cases were observed during 6-7 years of follow-up, respectively. Both oxidative stress biomarkers and the d-ROMs-to-TTL ratio were statistically significantly associated with all-cause mortality in both cohorts, and the pooled hazard ratios (HRs) and 95% CIs for top versus bottom tertiles were 2.10 (95% CI 1.43, 3.09) for d-ROMs levels, 0.59 (0.40, 0.87) for TTLs, and 2.50 (1.86, 3.36) for d-ROMs-to-TTL ratio. The d-ROMs-to-TTL ratio was also statistically significantly associated with incident MCE for top versus bottom tertile (1.65 [1.07, 2.54]), but this association did not persist after additional adjustment for chronic diseases. No associations with cancer were detected. - CONCLUSIONS: The observed strong associations of both biomarkers with mortality suggest an important contribution of an imbalanced redox system to the premature mortality of patients with diabetes.